THE EFFECT OF STORAGE ON THE NUTRITIONAL VALUE OF ADANSONIA DIGITATA L. LEAVES - Edogbanya, P. R. O; Abah, G; Yaro, C. A (university of el oued/جامعة الوادي, 2021)
Adansonia digitata L. leaves are used as vegetables in some parts of Africa. However, the leaves are not available all-year-round, so they are usually harvested, dried, and stored. In this research, the effect of storage on some nutritional components of Adansonia digitata leaves was studied. Proximate constituents, antinutrients, vitamins and minerals of leaves were determined using appropriate methods at week 0 (immediately after preparation of sample) and week 4 (after storage). Student’s T-test was used to compare the means of the various parameters measured at week 0 and week 4. The results revealed that powdered dried Adansonia digitata leaves was still viable as a good source of nutrients after four weeks of storage and some of its nutritional constituents were even improved.
Article
Keywords: Adansonia digitata, antinutrients, minerals, nutritional value, proximate, storage, vitamins